Updated nationally determined contributions collectively raise ambition levels but need strengthening further to keep Paris goals within reach - den Elzen, Michel G. J.; Dafnomilis, Ioannis; Forsell, Nicklas; Fragkos, Panagiotis; Fragkiadakis, Kostas; Höhne, Niklas; Kuramochi, Takeshi; Nascimento, Leonardo; Roelfsema, Mark; van Soest, Heleen; Sperling, Frank (Mitigation and adaptation strategies for global change, 2022)
By January 2022, 156 countries had submitted new or updated nationally determined contributions (NDCs) under the Paris Agreement. This study analyses the greenhouse gas (GHG) emissions and macroeconomic impacts of the new NDCs. The total impact of the updated unconditional and conditional NDCs of these countries on global emission levels by 2030 is an additional reduction of about 3.8 and 3.9 GtCO 2 eq, respectively, compared to the previously submitted NDCs as of October 2020. However, this total reduction must be about three times greater to be consistent with keeping global temperature increase to well below 2 °C, and even seven times greater for 1.5 °C. Nine G20 economies have pledged stronger emission reduction targets for 2030 in their updated NDCs, leading to additional aggregated GHG emission reductions of about 3.3 GtCO 2 eq, compared to those in the previous NDCs. The socio-economic impacts of the updated NDCs are limited in major economies and largely depend on the emission reduction effort included in the NDCs. However, two G20 economies have submitted new targets that will lead to an increase in emissions of about 0.3 GtCO 2 eq, compared to their previous NDCs. The updated NDCs of non-G20 economies contain further net reductions. We conclude that countries should strongly increase the ambition levels of their updated NDC submissions to keep the climate goals of the Paris Agreement within reach.